Answer: (4, -9)
Explanation:
Use elimination method. Manipulate one (or both) equations to eliminate one of the variables and solve for the remaining variable. I will be eliminating y
6x + y = 15 → 2(6x + y = 15) → 12x + 2y = 30
-7x - 2y = -10 → 1(-7x + 2y = -10) → -7x - 2y = -10
5x = 20
x = 4
Next, replace "x" with "4" into either equation and solve for y.
6(4) + y = 15
24 + y = 15
y = -9
Check:
Plug in x = 4 and y = -9 into the other equation to verify it makes a true statement.
-7x - 2y = -10
-7(4) - 2(-9) = -10
-28 - -18 = -10
-28 + 18 = -10
-10 = -10
![\checkmark](https://img.qammunity.org/2020/formulas/mathematics/middle-school/nk83tkgpik4r2dqvr5rpxy38c0h5cnew6l.png)